Răspuns :
1. L = 4 cm
2l = 4cm ; l = 2 cm
aria = L · l = 4 cm · 2 cm = 8 cm²
2. l = 2√3 cm
ariaΔ echil . = l²√3 /4 = ( 2√3) ² ·√3 / 4 = 4 ·3·√3 / 4 = 3√3 cm²
sau aria = baza ·inaltimea / 2 = l · h / 2 = 2√3 · h / 2 = √3 · h
√3cm · h = 3·√3 cm²
h = 3 cm
2l = 4cm ; l = 2 cm
aria = L · l = 4 cm · 2 cm = 8 cm²
2. l = 2√3 cm
ariaΔ echil . = l²√3 /4 = ( 2√3) ² ·√3 / 4 = 4 ·3·√3 / 4 = 3√3 cm²
sau aria = baza ·inaltimea / 2 = l · h / 2 = 2√3 · h / 2 = √3 · h
√3cm · h = 3·√3 cm²
h = 3 cm
1. L = 4 cm
2l = 4cm ; l = 2 cm
aria = L · l = 4 cm · 2 cm = 8 cm²
2. l = 2√3 cm
ariaΔ echil . = l²√3 /4 = ( 2√3) ² ·√3 / 4 = 4 ·3·√3 / 4 = 3√3 cm²
sau aria = baza ·inaltimea / 2 = l · h / 2 = 2√3 · h / 2 = √3 · h
√3cm · h = 3·√3 cm²
h = 3 cm